(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Modern world is full of hassles, deadlines, frustrations and demands, where stress is common for everyone. Stress is a general human phenomena & a regular part of person’s life from which nobody can get out of it. It is normal in bad situations or any tentative environment, but it becomes difficult when environmental stresses increase a person’s adaptive capacity to cope. Objective: The main purpose of this study is to find out the stress among parents of secondary school children, to assess the stress between the working and non-working parents of the secondary school children and to study the relationship between the level of parental stress and family environment for working and non-working parents. Method: Considering the demand of the objectives the researcher has selected 20 mothers of secondary school children (10 working mother and 10 non-working mothers). Parenting Stress Scale consisting of 18 items developed by Abidin, 1990 and Family Environment Scale developed by Sanjay Vohra 1997 have been used as data collection tools. Descriptive Statistics and t Test and Pearson Correlation Coefficient have been used for the data analysis. Findings: It has been revealed that working mothers experience higher level of Stress as compared to the non-working mothers and there is no significant difference functioning and collaboration of working and non-working women in family functioning.